Ice loading on podded propeller systems: preliminary test results - Rowell, B.; Duffy, D. (National Research Council of Canada. Institute for Ocean Technology, 2003)
With the increased interest in arctic shipping the number of vessels navigating in the arctic or being constructed with capabilities do so, is rapidly increasing. Thus this report outlines some of the results obtained during the first phase of testing here at the Institute for Ocean Technology (IOT) involving podded propellers in ice, and also details some of the preparation that has been completed for the second phase of testing. The analysis presented includes systematically determining at what instances and relative positions the apparatus experiences its maximum loading. The analysis shows that the maximum and minimum forces on the apparatus occur as one of the propeller blades is entering or exiting the ice respectively. Also, this report outlines the work that has been completed in preparation for the second phase of testing. This includes conducting a temperature sensitivity analysis for the AMTI six component load cells that were used on the forward and aft bearings and the set up for the global dynamometer calibration. NRC publication: Yes